2015
DOI: 10.4314/wsa.v41i4.06
|View full text |Cite
|
Sign up to set email alerts
|

Water use characteristics of a bambara groundnut (<i>Vigna subterranea</i> L. Verdc) landrace during seedling establishment

Abstract: Bambara groundnut is slow to establish and this has negative implications for total water use. Consideration of bambara groundnut as a water-efficient crop for dry areas will benefit from an understanding of water use efficiency and water use characteristics during establishment. We investigated whether there is an association between seed-coat colour of bambara groundnut seeds and water use efficiency. A secondary objective was to determine physiological and metabolic responses of bambara groundnut to termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
(13 reference statements)
1
11
0
Order By: Relevance
“…In the last 30 years, drought breeding work on bambara groundnut has been limited and largely focused and elucidated by above ground shoot morpho-physiological studies [11,13,14,16,19,[36][37][38][39][40][41][42]. In order to fully understand and better manipulate the ability to tolerate water-limited conditions, the range of both above-and belowground variation present in bambara groundnut germplasm needs to be explored [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 30 years, drought breeding work on bambara groundnut has been limited and largely focused and elucidated by above ground shoot morpho-physiological studies [11,13,14,16,19,[36][37][38][39][40][41][42]. In order to fully understand and better manipulate the ability to tolerate water-limited conditions, the range of both above-and belowground variation present in bambara groundnut germplasm needs to be explored [43].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increasing shortage of agricultural water and that no single shoot trait has yet been identified for its unique and dominant contribution to drought resistance [8][9][10][11][12][13][14][15][16][17][18][19], current bambara groundnut breeding efforts could investigate root system function and its manipulation in order to improve water and nutrient capture [20][21][22]. Bambara groundnut genotypes, such as S19-3 (from Namibia) are promising candidates for investigating and expanding plant ideotypes suited for dry environments [11,23].…”
Section: Introductionmentioning
confidence: 99%
“…Drought-resistance mechanisms in bambara groundnut have been elucidated by several studies in the last 30 years (Collinson et al 1997(Collinson et al , 1999Jorgensen et al 2010;Vurayai et al 2011;Laary et al 2012;Al Shareef et al 2014;Chibarabada et al 2015;Berchie et al 2016;Nautiyal et al 2017). Studies by Collinson et al (1997) indicated that bambara groundnut can maintain leaf turgor pressure by osmotic adjustment, reduced leaf area, and operational stomatal regulation.…”
Section: Bambara Groundnut-a Drought Resilient Cropmentioning
confidence: 99%
“…However, the degree of drought resistance varies between landraces and their place of origin; the severity and velocity of the drought and phenological stage effected (Collinson et al 1997(Collinson et al , 1999Jorgensen et al 2010;Vurayai et al 2011;Laary et al 2012;Al Shareef et al 2014;Chibarabada et al 2015;Nautiyal et al 2017). For example, Berchie et al (2012) evaluated a number of landraces of bambara groundnuts for their resistance to drought and heat and reported that some landraces could withstand 120 days of drought when irrigation was stopped at 30 DAP.…”
Section: Bambara Groundnut-a Drought Resilient Cropmentioning
confidence: 99%
“…To date, there has been separate attempts by crop scientists [16][17][18][19][20][21][22] and nutritionists [11][12][13] to address the knowledge gap on legumes. These efforts have been disciplinary and the information is yet to be consolidated so as to make meaningful impact on policy.…”
Section: Introductionmentioning
confidence: 99%